PENGARUH PEMBELAJARAN KEWIRAUSAHAAN TERHADAP MOTIVASI BERWIRAUSAHA - Reza Fahmi (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2012)
This study aims to explain the influence of entrepreneurship learning towards motivation to conduct business among students of Faculty of Ushuluddin at the Imam Bonjol State Institute of Islamic Studies of Padang. Data for this study was gathered through a population of students from four departments within the faculty, namely: Psikologi Islam (PI), Tafsir Hadist (TH), Perbandingan Agama (PA), Aqidah Filsafat (AF). Off the population, 92 students were chosen for the sample. Observation, questionnaire, and documentation were employed as the technique of data gathering. The findings show that there was a significant influence between the entrepreneurship learning and motivation to conduct business among students of Faculty of Ushuluddin IAIN Imam Bonjol Padang. =========================================== Penelitian ini bertujuan untuk menjelaskan pengaruh pembelajaran kewirausahaan terhadap motivasi berwirausaha mahasiswa Fakultas Ushuluddin Institut Agama Islam Negeri (IAIN) Imam Bonjol Padang. Data penelitian ini diperoleh dari responden yang berasal dari Fakultas Ushuluddin IAIN Imam Bonjol Padang, yang terdiri dari empat jurusan: Psikologi Islam (PI), Tafsir Hadist (TH), Perbandingan Agama (PA), Aqidah Filsafat (AF) dengan jumlah sampel sebanyak 92 orang. Pengumpulan data dilakukan dengan observasi langsung, angket dan dokumentasi. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan antara pembelajaran kewirausahaan dengan motivasi berwirausaha mahasiswa Fakultas Ushuluddin IAIN Imam Bonjol Padang.